A DNA‐Micropatterned Surface for Propagating Biomolecular Signals by Positional on‐off Assembly of Catalytic Nanocompartments. Issue 13 (22nd July 2022) - Maffeis, Viviana; Hürlimann, Dimitri; Krywko‐Cendrowska, Agata; Schoenenberger, Cora‐Ann; Housecroft, Catherine E.; Palivan, Cornelia G.
Abstract: Signal transduction is pivotal for the transfer of information between and within living cells. The composition and spatial organization of specified compartments are key to propagating soluble signals. Here, a high‐throughput platform mimicking multistep signal transduction which is based on a geometrically defined array of immobilized catalytic nanocompartments (CNCs) that consist of distinct polymeric nanoassemblies encapsulating enzymes and DNA or enzymes alone is presented. The dual role of single entities or tandem CNCs in providing confined but communicating spaces for complex metabolic reactions and in protecting encapsulated compounds from denaturation is explored. To support a controlled spatial organization of CNCs, CNCs are patterned by means of DNA hybridization to a microprinted glass surface. Specifically, CNC‐functionalized DNA microarrays are produced where individual reaction compartments are kept in close proximity by a distinct geometrical arrangement to promote effective communication. Besides a remarkable versatility and robustness, the most prominent feature of this platform is the reversibility of DNA‐mediated CNC‐anchoring which renders it reusable. Micropatterns of polymer‐based nanocompartment assemblies offer an ideal scaffold for the development of the next generation responsive and communicative soft‐matter analytical devices for applications in catalysis and medicine. Abstract : Spatially organized catalytic nanocompartments on DNA microarrays promote effective communication by propagating regulatory inputs and soluble signals. Such platforms are reusable by means of an immobilization strategy that allows multiple cycles of compartment attachment and detachment enabling repeated measurements within a few hours.